AB0395 Systemic osteoporosis and its relationship with disease activity in patients with early arthritis. (23rd January 2014) - del Olmo, L.; Aguado, P.; Coya, J.; Nuño, L.; Lojo, L.; Balsa, A.; Martín Mola, E.
Abstract : Background: The etiopathogenesis of bone loss seen in patients with rheumatoid arthritis (RA) is multifactorial. Factors that are intrinsic to the individual (age, gender), as well as disease- and treatment-related factors play a role. Longitudinal studies demonstrate that systemic bone loss occurs primarily in the initial stages of the disease and may be related to disease activity. Establishing bone status in patients with early arthritis (EA) may help to understand the true magnitude of osteoporosis (OP) in this arthropathy Objectives: To study systemic bone involvement in patients with EA and to establish the relationship with the disease's inflammatory activity Methods: This is a prospective study which including 113 patients from our EA Clinic with a disease duration from onset of symptoms of less than one year and without previous treatment. At the baseline visit we recorder: sociodemographic and anthropometric data, OP risk factors, bone metabolism laboratory parameters, radiography of the dorsolumbar spine, hands and feet and bone densitometry (Hologic QDR-4500) in the hip (femoral neck, FN) and lumbar spine (LS). The FRAX Index was established in patients over 40 years of age. Clinical disease activity was scored based on pain, patient and physician scoring, number of tender and swollen joints, acute-phase reactants (ESR and CRP) and functional capacity (HAQ). Rheumatoid factor and anti-cyclic citrullinated peptide antibodies were determined. Descriptive analysis and correlation studies (Pearson and Spearman) were carried out Results: At the initial visit, 31 patients met the ACR 1987 diagnostic criteria for RA and 82 the undifferentiated arthritis. Ninety-three women (82.3%) were studied, 42 premenopausal (pre-M) and 49 postmenopausal (post-M), as well as 20 (17.7%) men. The mean age was 50.8±16.1 years and the mean disease duration was 19.19±20.51 weeks. The prevalence of densitometric OP was 23.9% (7.3% pre-M, 36.7% post-M, 26.3% men) and the prevalence for osteopenia was 21.1% (12.2% pre-M, 26.5% post-M, 21.7% men). Eigthy-four percent had insufficient vitamin D levels (<30 ng/ml), with no correlation found with their natural sources (intake of dairy P 0.93 and sun exposure P 0.98). Inflammatory disease activity showed a DAS28 of 4.55±1.41. In the subgroup analysis, the post-M showed a higher prevalence of OP (p<0.01) and greater disease activity as expressed by DAS28 (p<0.001). 55.7% of post-M subjects and 16.4% of men had FRAX>3% for hip fracture. A significant negative correlation was seen between PTH and T-score in LS (p<0.01) and FN (p<0.02). The DAS 28 and the ERS (inflammatory activity parameters) showed a significant inverse relationship with the T-score in FN (p<0.04 and p<0.021) Conclusions: In our patients with EA, inflammatory activity influences bone loss in the hip. The subgroup of post-M women showed a greater prevalence of OP and greater inflammatory disease activity. Early follow-up of inflammation and close monitoring of bone status in patients with EA is necessary Disclosure of Interest: None Declared